"It Was Time for Me to Go Home": Sense of Place and Belonging in Kent, Ohio (May 1-4, 1970) - Mapes, Jennifer; Koopman, Sara (GeoHumanities, 2025)
On May 4, 1970, Kent State University students attended a protest at the Victory Bell on the Kent State University Commons. The Ohio National Guard moved up a nearby hill then turned and opened fire on the remaining students, killing four and wounding nine. But the memories of Kent State students and Kent residents documented in oral histories collected by the university library tell a broader story that covers a greater distance over time and place. We asked: What do oral histories, when located on a map of the city, tell us about experiences of the May 4 shooting at Kent State? We mapped 172 oral histories through 474 place-based audio clips from May 1-4, 1970. We find that spatializing these stories offers a more nuanced and detailed story of how people in Kent experienced these events. The mapping produces a kaleidoscopic view of the events of May 4 and emphasizes the complexity of overlapping experiences. These stories illustrate how the shooting, and later reflections on the days leading up to it, severely disrupted the sense of place and home of both students and townspeople.